Can laparoscopic nerve-sparing ultra-radical hysterectomy play a role in locally advanced cervical cancer? A single-center retrospective study - Wei, Wei-wei; Zheng, Hong; Shao, Panqiu; Chen, Xia; Min, Yi-fei; Tang, Bin; Sun, Hui-ting; Chen, Ji-ming; Shi, Ru-xia (Frontiers in Oncology, 2022)
Objective: To investigate the outcomes of concurrent platinum-based chemoradiation therapy (CCRT), LNSURH, and open radical hysterectomy (ORH) on patients with locally advanced cervical carcinoma (LACC). Methods: Age, tumor size, overall survival (OS), disease-free survival (DFS), early and late morbidities were collected. 24 months after treatment, patients were asked a series of questions about urinary, bowel, and sexual function. Early morbidities were defined as those occurring during or within a month after treatment. Late morbidities and complications were sent a month after treatment. Results: Kaplan Meier curves revealed that there were no significant differences in OS and DFS among 3 groups (P = 0.106 for DFS, 0.190 for OS). The rates of early complications in CCRT group were comparable to operated groups (P = 0.46). But, late complications were significantly lower in ORH and LNSURH groups than in the CCRT group. The scores of urinary and bowel functions were restored to pretreatment state, although sexual function scores were not satisfactory. Conclusion: The treatments of CCRT, ORH, and LNSURH can be options for patients with LACC as their OS and DFS had no significant difference. Otherwise the LNSURH exhibited a lower incidence of late complications and a high sexual function scores.